An overview of in situ testing and geophysical methods to investigate municipal solid waste landfills - Juarez, Mariana Barbosa [UNESP]; Mondelli, Giulliana [UNESP]; Giacheti, Heraldo Luiz [UNESP] (Springer Nature, 2023)
Municipal solid waste (MSW) management is challenging as a whole. Global waste generation is expected to continue to increase in the coming years, and landfills are currently the primary destination. Therefore, the stability of these structures must be carefully evaluated to prevent failures and associated health and pollution risks, which implies the determination of waste properties using more reliable approaches. This paper presents a scoping review of field data from MSW landfills and outlines suggestions for future work. Studies published in the past twenty years were selected following a systematic search process in databases. Aspects discussed include (1) strength parameters and soil behavior type from in situ testing, (2) elastic moduli from seismic wave propagation, and (3) moisture content from geoelectrical measurements. Although the values of geotechnical parameters have varied due to waste heterogeneity and applied methods, the trends observed with depth and age could be compared. Research opportunities involve the spatial analysis of mechanical properties at a given site, seismic response of landfills with high organic content and saturation degree, interpretation of long-term resistivity monitoring, and combination of electrical properties to assess the degradation stages within the waste mass.
Keywords: Density; Geoelectrical; Landfill; Moisture content; Municipal solid waste; Seismic; Shear strength; Stiffness